The Origin of Catalytic Benzylic C−H Oxidation over a Redox‐Active Metal–Organic Framework. (4th June 2021) - Kimberley, Louis; Sheveleva, Alena M.; Li, Jiangnan; Carter, Joseph H.; Kang, Xinchen; Smith, Gemma L.; Han, Xue; Day, Sarah J.; Tang, Chiu C.; Tuna, Floriana; McInnes, Eric J. L.; Yang, Sihai; et al.
Abstract: Selective oxidation of benzylic C−H compounds to ketones is important for the production of a wide range of fine chemicals, and is often achieved using toxic or precious metal catalysts. Herein, we report the efficient oxidation of benzylic C−H groups in a broad range of substrates under mild conditions over a robust metal–organic framework material, MFM‐170, incorporating redox‐active [Cu2 II (O2 CR)4 ] paddlewheel nodes. A comprehensive investigation employing electron paramagnetic resonance (EPR) spectroscopy and synchrotron X‐ray diffraction has identified the critical role of the paddlewheel moiety in activating the oxidant t BuOOH (tert‐butyl hydroperoxide) via partial reduction to [Cu II Cu I (O2 CR)4 ] species. Abstract : The oxidation of benzylic C−H groups in a broad range of substrates under mild conditions has been achieved using a robust metal–organic framework, MFM‐170, incorporating redox‐active [Cu2 II (O2 CR)4 ] paddlewheel nodes. EPR spectroscopy and synchrotron X‐ray diffraction have identified the critical role of the paddlewheel moiety in activating the oxidant t BuOOH ( tert ‐butyl hydroperoxide) via partial reduction to [Cu II Cu I (O2 CR)4 ] species.